THE RELATIONSHIP OF PLAY ACTIVITIES IN COGNITIVE DEVELOPMENT OF CHILDREN AGE 1 - 2 YEARS OLD - Hanita Hanita (Universitas Sebelas Maret, 2020)
Parents, schools and government should pay great attention to early childhood education and knowledge. Early childhood is nurtured and stimulated according to the wishes and abilities of each child with the hope that they can grow accordingly and develop as they should. Play is every child's right. Playing is a land for children to express all forms of behavior that are fun and without coercion. Play has a role to support children's growth and development, especially in the development of cognitive aspects. This study identifies the role of play activities on knowledge of children aged 1-2 years. Quantitative research and using a simple paradigm of the relationship of two variables. The data analysis technique used in this study was the parametric correlation analysis perarson product moment. The results of the study The value of sig (0.003) <a then H0 is rejected. So that there is a correlation between the role of play activities and the cognitive development of children 1-2 years. The correlation coefficient value shows the effect of the role of playing activities on cognitive development of children 1-2 years of 0.598 or 59.8%. So that the correlation is 40.2%, maybe there is a relationship with other elements.